2018
DOI: 10.1186/s13640-018-0334-2
|View full text |Cite
|
Sign up to set email alerts
|

A smart intraocular pressure risk assessment framework using frontal eye image analysis

Abstract: Intraocular pressure (IOP) in general refers to the pressure in the eyes. Gradual increase of IOP and high IOP are conditions/symptoms that may lead to certain diseases such as glaucoma and therefore must be closely monitored. While the pressure in the eye increases, different parts of the eye may become affected until the eye parts are damaged. An effective way to prevent rise in eye pressure is by early detection. A new smart healthcare framework is presented to evaluate the intraocular pressure risk from fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Vision-based approaches such as image processing and machine learning techniques have been used to assist in detecting high eye pressure symptoms that may lead to Glaucoma. This research has been built on top of the preliminary data found in [13], [14], [46], [47] to assist clinicians and patients for early screening of IOP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vision-based approaches such as image processing and machine learning techniques have been used to assist in detecting high eye pressure symptoms that may lead to Glaucoma. This research has been built on top of the preliminary data found in [13], [14], [46], [47] to assist clinicians and patients for early screening of IOP.…”
Section: Discussionmentioning
confidence: 99%
“…Building over our work in [13], [14], this research studies several algorithms and certain algorithms are selected to direct this research to be automated such that it can eventually be applied on smart-phones. The main contributions of the proposed work can be specified in the following points: Proposing a new framework to help both ophthalmologists and high IOP candidates in the initial diagnosis of IOP early-on, as it is the most effective approach to prevent full or partial IOP/Glaucoma based vision loss.Introducing a novel vision-based architecture, structure and features for initial IOP screening using frontal eye images.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2 illustrates our proposed causal model for the Eye-SCOR framework. The factors deemed most important for Eye-SCOR have been selected as a result of comprehensively reviewing the literature related to causal models for healthcare applications [9] and specifically eye status monitoring systems [20,21]. The model carries hypothesized information among the factors and their inter-relationships.…”
Section: Methodology 21 Causal Modelmentioning
confidence: 99%
“…Automated decision support frameworks for smart healthcare monitoring rely on artificial intelligence (AI)-assisted models using machine/deep learning and/or signal/image processing, as well as data analysis techniques applied to the acquired digital health data. Examples include techniques monitoring heart status using electrocardiogram (ECG) signal [12], brain and mental status from electroencephalogram (EEG) signal [13,14], breathing and respiratory status from breathing sounds [15][16][17][18], skin lesion analysis from images [19], eye disease determination [7,[20][21][22][23][24], and so on, some of which have been translated into smartphone apps [10,25].…”
Section: Introduction 1background Literature and Motivationmentioning
confidence: 99%
See 1 more Smart Citation